Task-based Supplementary Instructional Materials in Learning Grade 10 Chemistry - Rodriguez, Nicoflor (Future Science / FSH-PH Publications, 2023)
This study aimed to develop and evaluate task-based supplementary instructional materials in learning Grade 10 Chemistry in selected junior high schools in District I of the Schools Division Office of Marikina City during the school year 2021 - 2022. This study utilized the descriptive method of research with the questionnaire as the data gathering instrument. The sources of data were the ten (10) experts and twenty (20) high school Science teachers from the Schools Division Office of Marikina City, who served as the evaluators of the developed task-based supplementary instructional materials. Five criteria, namely: instructional design and organization of material, instructional quality, assessment, format, and presentation were used to determine the acceptability of the developed task-based supplementary instructional materials. The statistical tools used in this study were weighted mean and t-test. The significant findings of the study based on the questions raised are both the Science teachers and the Science experts evaluated the developed task-based supplementary instructional materials as very satisfactory in terms of instructional design and organization of material, instructional quality, assessment, format, and presentation and there was no significant difference between the evaluations of Science teachers and Science experts on the developed task-based supplementary instructional materials based on instructional design and organization of material, instructional quality, assessment, format, and presentation.